Strategi Komunikasi Pemasaran PT. Halal Network International-Herba Penawar Al Wahida dalam Menarik Minat Konsumen di Kecamatan Hamparan Perak - Syahida, Akrima (Lembaga Yasin AlSys, 2023)
This study aims to obtain information about the marketing communication strategy of PT.Halal Network International-Herba Penawar Al Wahida in attracting consumer interest in the Silver expanse sub-district. The location of this research is precisely on Jl. Besar Klambir V, Hamparan Perak. This research is included in the qualitative descriptive research, because it aims to describe the condition of the phenomena in the field that occur at PT. HNI-HPAI in Hamparan Perak District and used data collection techniques in this study, namely by interview, observation, and documentation. The data sources in this study are Loyal Diamond Executive Director, Senior Director, Senior Manager and Consumers. The results showed that there were 4 communication strategies implemented by PT. HNI-HPAI in attracting consumer interest in Hamparan Perak District, and it can be concluded that according to the 4P marketing mix, namely Product, Price, Place, and Promotion, the factors that hinder marketing communication strategies HNI HPAI in attracting consumer interest, being rejected by consumers, internal problems, high prices and factors that support the HPAI HNI marketing communication strategy in attracting consumer interest, consumer testimonials, support systems, cashback according to the rank of HNI HPAI Stock Agent.